“Please learn from my mistakes”: the acute need for an entrepreneurial mindset in academic biosensor research - Heikenfeld, Jason (Frontiers in Sensors, 2024)
History is full of technological breakthroughs that arguably were first discovered because fundamental research was conducted without commercial influence. Fundamental research also plays an important role in producing the next genera@on of researchers. However, this ar@cle argues that research in general, and in par@cular biosensor research, is suffering from diminishing impact because of a lack of entrepreneurial mindset when defining research objec@ves. The story of the authors own biosensor research pathway is presented, and provides an exemplary case study of this larger problem. An entrepreneurial mindset enables a stronger founda@on even at the stage of research hypothesis forma@on: the need for the research is jus@fied; the research is not duplica@ve and is posi@oned to create new knowledge; the research product will be more readily translatable by industry. Most graduates in sensors research will work in industry, and therefore those students exposed to an entrepreneurial mindset will also start their careers with a more complete set of the skills that industry is looking for. Introduc@on: Academic researchers are mostly rewarded for publica@ons, cita@ons, and grant funding above other metrics. It is therefore expected that these top metrics strongly influence the forma@on of research